Coking coals of the Arctic zone of Russia - V.I. Vyalov; A.B. Gurevich; G.M. Volkova; D.A. Skiba; E.P. Shishov; A.A. Chernyshev (Georesursy, 2019)
Rational and cost-effective development of the richest hydrocarbon resources of the Arctic region of Russia is impossible without the resumption of solid fuel production. On the Arctic coast of Russia there is the largest base of coking coals of valuable ranks, which requires the study and active development in the framework of the overall strategy of development of fuel and energy resources of the Russian North and, in general, the fuel and energy complex of the country. The most valuable in quality and properties deposits and basins of coking coals of the Arctic zone of Russia are considered. Among them are the Taimyr, Tunguska, Zyryanka and Bering basins. The features of coal-bearing, matter-petrographic composition and quality, the basic properties of coal of basins and promising fields, their resource and geological characteristics are given. Recommendations for their further study are given, the prospects of their development and transportation of coal along the Northern Passage are discussed.